2015
DOI: 10.1080/13691058.2015.1083122
|View full text |Cite
|
Sign up to set email alerts
|

Gatekeeping and its impact on father involvement among Black South Africans in rural KwaZulu-Natal

Abstract: Involved and caring fatherhood contributes to the health and wellbeing of children, women and men. The corollary is also true - men, women and children are affected when fathers are not involved or supportive of their children. Many factors affect fathers' involvement, including women's attitudes, the history and nature of the relationship between mother and father, and the cultural context. This study explores gatekeeping and its impact on father involvement among Black South Africans in rural KwaZulu-Natal. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 23 publications
0
21
0
5
Order By: Relevance
“…With these aims, the current study increases insight into the mechanisms through which gender inequalities in both work and family domains may be strengthened by intensive mothering discourses. In the family domain, pressure to be a perfect mother may reinforce women’s higher investment in childcare tasks as compared to men ( European Institute for Gender Equality, 2015 ), since maternal gatekeeping behaviors increase women’s second shift ( Hochschild and Machung, 2012 ) and restrict men’s opportunities to invest in domestic tasks ( Mcbride et al, 2005 ; Gaunt, 2008 ). In the work domain, pressure to be a perfect mother may reinforce gender inequalities by contributing to women’s underrepresentation in positions of power, lower work participation rates, and lower pay ( European Union, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…With these aims, the current study increases insight into the mechanisms through which gender inequalities in both work and family domains may be strengthened by intensive mothering discourses. In the family domain, pressure to be a perfect mother may reinforce women’s higher investment in childcare tasks as compared to men ( European Institute for Gender Equality, 2015 ), since maternal gatekeeping behaviors increase women’s second shift ( Hochschild and Machung, 2012 ) and restrict men’s opportunities to invest in domestic tasks ( Mcbride et al, 2005 ; Gaunt, 2008 ). In the work domain, pressure to be a perfect mother may reinforce gender inequalities by contributing to women’s underrepresentation in positions of power, lower work participation rates, and lower pay ( European Union, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies use marital status as the indicator of regular partnerships in heterosexual couples. However, in the surveillance area, only 10% of women aged 20 to 45 years were currently married in 2009 while more than half of men and women aged <39 years experienced at least one formation of a conjugal relationship . Lastly, the proportions of concurrent stable partnerships or causal sexual partnerships were quite low among those in stable partnerships.…”
Section: Discussionmentioning
confidence: 97%
“…Krampe (2009) reported that the father-child relationship is very important, contrary to what had been previously argued, and that mothers can reinforce or erode the psychological presence of the father presence in their children's minds. National and international research findings emphasizing based upon a systemic and multi-dimensional evaluation of the father-child relationship report that mothers assume a facilitator or inhibitor (=maternal gatekeeping) role in the development of that relationship (Allen & Hawkins, 1999;Makusha & Richter, 2016;Puhman & Pasley, 2013, 2017Schoppe-Sullivan et al, 2008;Trinder, 2008;Tu et al, 2014). Gazi (2019) reported that there is a negative correlation between maternal gatekeeping and father involvement/the father-adolescent relationship, and that maternal gatekeeping predicted the father's involvement negatively.…”
Section: Discussionmentioning
confidence: 99%